Photoluminescent properties of crystalline solid solution Zn₁₋ xMgxSe:Cr²⁺, a new active material for tunable IR lasers - Kovalenko, N.O.; Zagoruiko, Yu.A.; Fedorenko, O.O.; Kuzminov, E.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Considered in this work are the luminescent properties of new active material Zn₁₋xMgxSe :Cr²⁺ for tunable IR lasers. Measured in Zn₀.₇₅Mg₀.₂₅Se : Cr²⁺ is the spectrum of IR luminescence excitation, and shown is the possibility of excitation in the visible spectral range. It is established that the luminescence band maximum is shifted by
approximately 200 nm in comparison with that of ZnSe:Cr²⁺. Presented are the measured time characteristics of photoluminescence excited in the visible (550 nm) and IR (1800 nm) spectral regions.